2018
DOI: 10.1111/jfpe.12947
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound and microwave assisted oil extraction from sea buckthorn seeds by response surface methodology

Abstract: Sea buckthorn (SB) seeds were used as raw material to obtain SB oil using two extraction methods: ultrasound and microwave assisted extraction. The favorable experimental conditions that maximize the extraction efficiency were investigated by applying response surface methodology (RSM). The selected key independent variables were ultrasonic intensity (UI), temperature, and time for ultrasound assisted extraction (UAE) and microwave power, time, and solid/liquid ratio for microwave assisted extraction (MAE). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…Moreover, the researchers reported gains in extraction time because optimum yield was achieved at 60 min for UAE while the same yield was obtained at 90 min for solvent extraction. Isopencu et al [59] optimized ultrasonic intensity (UI), temperature, and time in the extraction of sea buckthorn oil. For optimized extraction, operation conditions were 13.77 W/cm 2 UI, 40 • C, and 10 min extraction time for UAE.…”
Section: Ultrasound Assisted Extraction (Uae)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the researchers reported gains in extraction time because optimum yield was achieved at 60 min for UAE while the same yield was obtained at 90 min for solvent extraction. Isopencu et al [59] optimized ultrasonic intensity (UI), temperature, and time in the extraction of sea buckthorn oil. For optimized extraction, operation conditions were 13.77 W/cm 2 UI, 40 • C, and 10 min extraction time for UAE.…”
Section: Ultrasound Assisted Extraction (Uae)mentioning
confidence: 99%
“…Ionic conduction caused by the electrophoretic migration and the dipole rotation of realignment of ions under an applied electromagnetic field results in an increase in temperature of the extraction medium [28,66]. MAE is greatly influenced by the solubility of the compounds of interest in the solvent, partition coefficient, mass diffusivity, and the dielectric properties of the feedstock and the solvent [59]. Mgudu et al [66] investigated the effect of the microwave treatment on the yield and quality of the oil obtained from castor beans and showed that the microwave treatment gave optimum yields of 44.34% at a power of 280 W after 120 s. Mosquera et al [67] also reported that a better quality palm oil with a lower unsaturated fatty acid content even though a lower yield was obtained from the MAE process compared to expeller press and solid-liquid extraction.…”
Section: Microwave Assisted Extractionmentioning
confidence: 99%
“…The most common method to obtain extracts from plants is solvent extraction. However, in recent years different extraction techniques were applied for the phytochemical extraction, such as ultrasound-assisted extraction (UAE), microwave-assisted extraction (MAE), either separate or simultaneous (Asofiei et al, 2016;Chemat et al, 2012;Isopencu et al, 2019;Li et al, 2018). It was demonstrated that the ultrasound-assisted extraction with frequencies higher than 20 kHz has an essential role in the facilitation of the extraction of the organic compounds using different solvents (Roidaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be pointed out that this extraction approach consumes large quantities of solvents and extraction time (Ruesgas‐Ramon, Figueroa‐Espinoza, & Durand, ). In the face of the drawbacks of CSE, the researchers have developed a new technique called the ultrasonic‐assisted extraction (UAE) (Isopencu et al, ; Naffati, Vladic, Pavlic, & Vidovic, ). It can be shown that this method can not only reduce the solvent consumption, but also greatly improve the extraction efficiency (Giuseppe et al, ; Liliana, Adina, Irina, & Valentin, ; Ma, Chen, Liu, & Ye, ; Naffati et al, ).…”
Section: Introductionmentioning
confidence: 99%